Biventricular Heart Remodeling After Percutaneous or Surgical Pulmonary Valve Implantation: Evaluation by Cardiac Magnetic Resonance. Issue 6 (November 2017) - Secchi, Francesco; Resta, Elda C.; Cannaò, Paola M.; Pluchinotta, Francesca; Piazza, Luciane; Butera, Gianfranco; Carminati, Mario; Sardanelli, Francesco
Abstract : Purpose: The aim of this study was to evaluate the impact of percutaneous pulmonary valve implantation (PPVI) and surgical pulmonary valve replacement (SPVR) on biventricular and pulmonary valve function using cardiac magnetic resonance. Materials and Methods: Thirty-five patients aged 20±8 years (mean±SD) underwent PPVI, whereas 16 patients aged 30±11 years underwent SPVR. Cardiac magnetic resonance examinations were performed before and after the procedures with an average follow-up interval of 10 months. Cine steady-state free precession sequences for cardiac function and phase-contrast sequences for pulmonary flow were performed. The right ventricle (RV) and left ventricle (LV) functions were evaluated using a dedicated software. Results: The RV end-diastolic volume index (mL/m 2 ) decreased significantly after PPVI and SPVR, from 74 to 64 ( P =0.030) and from 137 to 83 ( P =0.001), respectively. The RV ejection fraction increased significantly after SPVR, from 47% to 53% ( P =0.038). The LV end-diastolic volume index increased significantly after PPVI, from 66 to 76 mL/m 2 ( P <0.001). The LV stroke volume index increased significantly after PPVI, from 34 to 43 mL/m 2 ( P =0.004). The analysis of bivariate correlations showed that in patients undergoing SPVR the RV changes after the procedure were positively correlated to LV changes in terms of end-systolic volume index ( r =0587; P =0.017) and ejection fraction ( r =0.681; P =0.004). Conclusions: A RV volumetric reduction and a positive effect on ventricular-ventricular interaction were observed after both PPVI and SPVR. After PPVI, a positive volumetric LV remodeling was found. No LV remodeling was found after SPVR. After both procedures, the replaced pulmonary valve functioned well.